2016
DOI: 10.1016/j.jclinepi.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators perceived by physicians when using prediction models in practice

Abstract: Combining probabilistic output of the model with their clinical experience may be difficult for physicians, especially when their decision-making process is mostly intuitive. Adding recommendations to predicted risks (directive approach) was considered an important step to facilitate the uptake of a prediction tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 38 publications
2
62
0
2
Order By: Relevance
“…The 95% CIs were calculated from the covariance matrix for the variable study, allocation group, predicted probability, and their interaction terms. Further methodologic information and the numerical results of the regression models are available in Additional file 1 way to decrease the required cognitive effort and increase the ease of use of the prediction tool, as supported by our results (Table 3, F.1) [38]. This does not mean that probabilities alone cannot be useful.…”
Section: Addressing the Physician's Perspectivesupporting
confidence: 62%
“…The 95% CIs were calculated from the covariance matrix for the variable study, allocation group, predicted probability, and their interaction terms. Further methodologic information and the numerical results of the regression models are available in Additional file 1 way to decrease the required cognitive effort and increase the ease of use of the prediction tool, as supported by our results (Table 3, F.1) [38]. This does not mean that probabilities alone cannot be useful.…”
Section: Addressing the Physician's Perspectivesupporting
confidence: 62%
“…Compliance with institutional protocols is improved somewhat by educational strategies and decision prompting. 77,78 Kappen et al 79 recently reported their investigation into the failure of risk-prompting strategy for PONV to influence patient outcome. The reluctance of the clinicians to change practice was based in part on risk management, ie, the lack of risk-benefit consideration for drugs.…”
Section: Implementation Gapsmentioning
confidence: 99%
“…Additional factors were the low priority given to PONV as an important health care outcome and the reliance on intuition to make decisions regarding prophylaxis. 79…”
Section: Implementation Gapsmentioning
confidence: 99%
“…Poor knowledge about PONV management negatively affects the patient, but there are situations in which health professionals can't intervene PONV even if the factors causing nausea, and vomiting are identified by professionals (5). Knowledge and perception of health professionals regarding the consequences of PONV are limited, which leads them not to give attention to prevention strategies (6).…”
Section: Introductionmentioning
confidence: 99%